Fungsi Tari Wura Bongi Monca di Desa Karumbu, Kecamatan Langgudu, Kabupaten Bima, Nusa Tenggara Barat - Dayantri, Rima; Winarti, Tutik; Supriyanti, Supriyanti (Institut Seni Indonesia Yogyakarta, 2024)
Tulisan ini mengupas fungsi Tari Wura Bongi Monca di Desa Karumbu Kecamatan Langgudu, Kabupaten Bima, Nusa Tenggara Barat. Tari Wura Bongi Monca adalah tarian penyambutan tamu, tarian selingan di tengah dan akhir acara, dan tarian hiburan untuk memeriahkan acara. Penelitian ini menggunakan pendekatan antropologi tari. Tipologi fungsi tari dirumuskan dalam enam kategori, yaitu tari sebagai refleksi dan legitimasi tatanan sosial, wahana ekspresi ritual sekuler dan keagamaan, hiburan sosial atau kegiatan rekreasi, saluran atau pelepasan spiritual, pencerminan nilai estetis atau suatu kegiatan estetis itu sendiri, dan sebagai pencerminan pola kegiatan ekonomi untuk menunjang kehidupan. Penelitian ini menunjukkan bahwa fungsi tari Wura Bongi Monca sebagai bagian penting dalam memenuhi kebutuhan kesenian untuk hiburan, cerminan nilai estetis, cerminan pola kegiatan ekonomi, refleksi, wahana ekspresi ritual dan keagamaan, dan sebagai saluran pelepasan spritual. The Function of the Wura Bongi Monca Dance in Karumbu Village, Langgudu Subdistrict, Bima Regency, West Nusa Tenggara.This paper examines the functions of the Wura Bongi Monca Dance in Karumbu Village, Langgudu Subdistrict, Bima Regency, West Nusa Tenggara. The Wura Bongi Monca Dance serves as a welcoming dance for guests, an interlude performance during and at the end of events, and as entertainment to enliven festivities. This study adopts an anthropological approach to dance. The typology of dance functions is categorized into six areas: dance as a reflection and legitimization of social order, a medium for secular and religious ritual expression, social entertainment or recreational activity, a channel for spiritual release, a reflection of aesthetic values or aesthetic activity itself, and as a reflection of economic activities supporting livelihoods. The study demonstrates that the Wura Bongi Monca Dance plays a crucial role in fulfilling artistic needs for entertainment, reflecting aesthetic values, economic activity patterns, and social order, serving as a medium for ritual and religious expression, and as a channel for spiritual release.